Population Genetic Analysis of Fusarium decemcellulare, a Guaraná Pathogen, Reveals High Genetic Diversity in the Amazonas State, Brazil - Queiroz, Claudia A. Claudia A.; Caniato, Fernanda F. Fernanda F.; Siqueira, Vanessa K S Vanessa K S; de Moraes Catarino, Aricléia Aricléia; Hanada, Rogério E Rogério E; O'Donnell, Kerry Kerry; Laraba, Imane Imane; Rehner, Stephen A. Stephen A.; Sousa, Nelcimar Reis Nelcimar Reis; Silva, Gilvan F. (Plant Disease, 2023)
Guaraná is indigenous to the Brazilian Amazon where it has cultural and agroeconomic significance. However, its cultivation is constrained by a disease termed oversprouting of guaraná caused by Fusarium decemcellulare, with yield losses reaching as high as 100%. The disease can affect different parts of the plant, causing floral hypertrophy and hyperplasia, stem galls, and oversprouting of vegetative buds. To date, no study has been conducted characterizing the genetic diversity and population structure of this pathogen. Here, we report genetic diversity and genetic structure among 224 isolates from eight guaraná production areas of Amazonas State, Brazil, that were genotyped using a set of 10 inter-simple-sequence repeat (ISSR) markers. Despite moderate gene diversity (Hexp = 0.21 to 0.32), genotypic diversity was at or near maximum (223 multilocus genotypes among 224 isolates). Population genetic analysis of the 10 ISSR marker fragments with STRUCTURE software identified two populations designated C1 and C2 within the F. decemcellulare collection from the eight sites. Likewise, UPGMA hierarchical clustering and discriminant analysis of principal components of the strains from guaraná resolved these same two groups. Analysis of molecular variance demonstrated that 71% of genetic diversity occurred within the C1 and C2 populations. A pairwise comparison of sampling sites for both genetic populations revealed that 59 of 66 were differentiated from one another (P < 0.05), and high and significant gene flow was detected only between sampling sites assigned to the same genetic population. The presence of MAT1-1 and MAT1-2 strains, in conjunction with the high genotypic diversity and no significant linkage disequilibrium, suggests that each population of F. decemcellulare might be undergoing sexual reproduction. Isolation by distance was not observed (R2 = 0.02885, P > 0.05), which suggests that human-mediated movement of seedlings may have played a role in shaping the F. decemcellulare genetic structure in Amazonas State, Brazil.
Keywords: Genetic; Guaraná; Agriculture